Membangun Model Prediksi Churn Pelanggan yang Akurat: Studi Kasus tentang TELCO Company - Andy Hermawan; Nila Rusiardi Jayanti; Zia Tabaruk; Faizal Lutfi Yoga Triadi; Aji Saputra; M.Rahmat Hidayat Syachrudin (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Customer churn prediction models have become an important tool in the telecommunications industry to reduce churn rates and improve customer retention. This research focuses on building an accurate customer churn prediction model using machine learning algorithms for TELCO Company. By applying diverse feature engineering techniques and prediction models such as RandomForestClassifier, DecisionTreeClassifier, and XGBoost, this study showcases a significant improvement in prediction accuracy compared to previously implemented rule-based methods. The findings of this research allow TELCO Company to identify high-risk customers more effectively and implement targeted retention strategies. Results show that the resulting model can identify customers at risk of churn more effectively, enabling more targeted retention actions..